Biochemical Origin of Raman-Based Diagnostics of Huanglongbing in Grapefruit Trees - Dou, Tianyi; Sanchez, Lee; Irigoyen, Sonia; Goff, Nicolas; Niraula, Prakash; Mandadi, Kranthi; Kurouski, Dmitry (Frontiers in Plant Science, 2021)
Biotic and abiotic stresses cause substantial changes in plant biochemistry. These changes are typically revealed by high-performance liquid chromatography (HPLC) and mass-spectroscopy coupled HPLC (HPLC-MS). This information can be used to determine underlying molecular mechanisms of biotic and abiotic stresses in plants. A growing body of evidence suggests that changes in plant biochemistry can be probed by Raman spectroscopy, an emerging analytical technique that is based on inelastic light scattering. Non-invasive and non-destructive detection and identification of these changes allow for the use of Raman spectroscopy for confirmatory diag-nostics of plant biotic and abiotic stresses. In this study, we couple HPLC and HPLC-MS findings on biochemi-cal changes caused by Candidatus Liberibacter spp. (Ca. L. asiaticus) in citrus trees to the spectroscopic signa-tures of plant leaves derived by Raman spectroscopy. Our results show that Ca. L. asiaticus causes an increase in hydroxycinnamates, the precursors of lignins, and flavones, as well as a decrease in the concentration of vio-laxanthin and lutein that are detected by Raman spectroscopy. These findings suggest that Ca. L. asiaticus in-duce a strong plant defense response that aims to exterminate bacteria present in the plant phloem. This work also suggest that Raman spectroscopy can be used to resolve stress-induced changes in plant biochemistry on the molecular level.